Influence of treatment of tobacco leaves with microwave radiation on quality indicators and quantitative composition of raw tobacco raw materials - L. P. Pestova; E. I. Vinevsky; A. V. Chernov (Новые технологии, 2020)
Technologies for obtaining expanded tobacco have been developed, which make it possible to increase the volume of tobacco leaves up to 50% and reduce the consumption of tobacco raw materials in the manufacture of smoking articles by up to 30%. However, they have a number of disadvantages, the main one being a decrease in the tasting evaluation of raw materials. The subject of the research is to determine the effect of microwave radiation when processing freshly harvested tobacco leaves on improving the qualitative and quantitative indicators of tobacco raw materials. The object of the research is freshly harvested leaves of three botanical varieties of tobacco grown at the experimental site of the Federal State Budgetary Scientific Institution «All-Russian Research Institute of tobacco, makhorka and tobacco products», harvested in the condition of technical maturity. The purpose of the research is to study the effect of microwave- radiation treatment of tobacco leaves during their post-harvest processing on the possibility of obtaining expanded tobacco and on the qualitative and quantitative composition of raw tobacco. The following has been established: the obtained raw tobacco in terms of dimensional characteristics is similar to expanded tobacco obtained under factory conditions; carbohydrate-protein ratio (Shmuk’s number) in comparison with the control on has increased 2,5–4,5 times, and the nicotine content has decreased 1,3–1,4 times; the conventional consumption of raw tobacco for the manufacture of cigarettes is reduced by 8 ... 17% in comparison with the control one, depending on the drying technology. The results of the studies have revealed the positive effect of microwave radiation when processing freshly harvested tobacco leaves on the improvement of the qualitative and quantitative indicators of raw tobacco.